The Vital Role Of Notaries In Ontology, Epistemology, And Axiology: Architect Of Legal Reality Formation, Guardian Of Information Validity, And Protector Of Moral Justice - Ghaffar Deprian (Leges Privatae, 2024)
This article discusses the vital role of notaries in the context of ontology, epistemology, and axiology as a legal profession that provides authentic document creation services. Notaries are not just deed writers, but architects of the formation of legal reality, maintain the validity of legal information, and follow ethical principles in legal services. By exploring the ontological dimension, notaries are considered as guardians of legal certainty and authentic deed makers who understand the existence and nature of justice. In epistemology, notaries are expected to have in-depth knowledge of legal provisions, ensure the correctness of legal information, and provide a deeper understanding of legal concepts. In axiology, notarial ethics reflect a commitment to avoid conflicts of interest, maintain integrity, and ensure legal services are performed in accordance with moral principles. By engaging these three perspectives, this article illustrates the urgency of notaries in maintaining the sustainability of the legal system and providing fair and balanced legal protection for society.